2020
DOI: 10.1177/1087054720950820
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Risky Behavior in ADHD: Insensitivity to its Risk or Fascination with its Potential Benefits?

Abstract: Objective: ADHD is linked to increased engagement in risky behavior (ERB). Recent work suggests that this link is mediated by the perceived benefits of the behaviors, but not by the perceived risks or the attitudes toward the risks. Here we examine this hypothesis, using the psychological risk-return and psychometric multidimensional measurement models. Method: Adults with or without ADHD completed questionnaires measuring the likelihood of different risky behaviors and the perceived risks and benefits ascribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…Even when controlling for overall level of sexual behavior, ADHD symptoms were positively correlated with RSB. In this study, researchers also inquired as to participants’ perceived benefits and risk of RSBs, and, consistent with research on broader risk-taking associated with ADHD ( Shoham et al, 2016 , 2021 ), found that ADHD symptomology positively correlated with participants’ perceived benefit, but not the perceived risk ( Spiegel & Pollak, 2019 ). Mediation analysis demonstrated an indirect pathway, where ADHD symptoms predicted greater perceived benefit of RSB, which subsequently predicted an increased probability of engaging in such behaviors.…”
Section: Domains Of Functional Impairmentsupporting
confidence: 76%
“…Even when controlling for overall level of sexual behavior, ADHD symptoms were positively correlated with RSB. In this study, researchers also inquired as to participants’ perceived benefits and risk of RSBs, and, consistent with research on broader risk-taking associated with ADHD ( Shoham et al, 2016 , 2021 ), found that ADHD symptomology positively correlated with participants’ perceived benefit, but not the perceived risk ( Spiegel & Pollak, 2019 ). Mediation analysis demonstrated an indirect pathway, where ADHD symptoms predicted greater perceived benefit of RSB, which subsequently predicted an increased probability of engaging in such behaviors.…”
Section: Domains Of Functional Impairmentsupporting
confidence: 76%
“…A short form of the Adult Risk-Taking Inventory (ARTI) was used to measure past engagement in risky behavior. The tool was validated in previous studies ( Shoham et al, 2020 , 2021 ). The short form consisted of 14 items probing for the frequency of engagement in relatively frequent activities (e.g., sunbathing without sunscreen, smoking marijuana) with respect to their frequency during the preceding year on a rating scale, ranging from 1 = “ Not at all ” to 7 = “ On a daily basis .” Previous work has shown that the ARTI has good reliability and validity.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents rated the extent to which a series of six attributes described them during six months reference period on a three-level response scale (0 = "not true", 1 = "somewhat true", or 2 = "certainly true"). A short form of the Adult Risk-Taking Inventory (ARTI) (20,21) was used to measure past engagement in risky behavior. The short form consists of 14 items probing for the frequency of engagement in relatively frequent activities (e.g., sunbathing without sunscreen, smoking marijuana) with respect to their frequency during the preceding year on a rating scale, ranging from 1 (Not at all) to 7 (On a daily basis).…”
Section: Behavioral and Personality Factorsmentioning
confidence: 99%